(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Regular physical activity has a substantial impact on lowering the risks associated with health. Aquatic training program can improve the physical function in humans and raise the quality of their lives in middle and older age .The study aimed to determine the effect of aqua aerobic training on body composition of middle age women of Manipur. Totally 40 women was randomly selected having an average age 39±2.16 years from Kakching Mayai Leikai, Kakching, Thoubal District, Manipur. They were randomly divided into two groups: Experimental group (those undertaking a aqua aerobic training program) and a control group with 20 participant in each group. The aqua aerobic training was assign to experimental group for 12 weeks series for five days per week while control group was not given any training . The training was given for 45 minutes with 15 minutes of warming up and cooling down .The subjects Body Mass Index (BMI) weight were measured automatically using a BWB-800 AS scale (Tanita), and height with HR-200 Stadiometer (Tanita). BMI was calculated as weight in kilograms divided by height squared (kg/m2) in meters. To estimate the body fat mass (BFM) four sites skinfold measurement were taken with skinfold Callipers. The four sites were triceps, abdominal, suprailiac and thigh, (BFM) body fat mass were measured with the Jackson and Pollock 4 site skinfold formula before and after the completion of aqua aerobic training program .The paired t-test and analysis of covariance ( ANCOVA) were used , the data analyzed with the help of SPSS (20 version ) software and the level of significance was set at 0.05 level of confidence. Results: After the 12 weeks of aqua aerobic training program, It shows the training group was significantly decrease in weight.